HUBUNGAN POWER LENGAN DAN KELENTUKAN PERGELANGAN TANGAN DENGAN KETEPATAN FREE THROW PADA SISWA EKSTRAKURIKULER BOLABASKET SMK KETINTANG SURABAYA - Bagaswani, Muhammad Padang; Dewi, Ratna Candra (Jurnal Kesehatan Olahraga, 2019)
This research was motivated by the basketball extracurricular in SMK Ketintang Surabaya which is still not optimal when following a few basketball matches held in Surabaya, especially when getting free throw during matches. The level of success is still not optimal, so there are still a number of things that cause shots to be less optimal free throw done. The type of research used in this study uses types analytic survey research. In this study using the cross approach sectional study to see the relationship between arm power and flexibility wrist against the accuracy of the free throw on basketball extracurricular SMK Ketintang Surabaya. The results of this study can be concluded that the correlation test results between variable power arm with the accuracy of the free throw indicates a relationship strong and unidirectional significance, while the correlation test results between variables wrist flexion with the accuracy of the free throw indicates a relationship significant and unidirectional direction in basketball games for students extracurricular at SMK Ketintang Surabaya.